Racial Disparities in Clinical Trial Enrollment Among Patients Diagnosed With Prostate Cancer: A Population-Based Cohort of Oncology Practices - Brett M. Wiesen; Thomas W. Flaig; Boris Gershman; Badrinath Konety; Adam Warren; Elizabeth Molina Kuna; Tyler Robin; Elizabeth R. Kessler; Corbin J. Eule; Benjamin N. Breyer; Justin Achua; Simon P. Kim (Advances in Urology)
Conclusion: While clinical trial enrollment remains low for men with advanced prostate cancer in this contemporary population-based cohort, rates of participation for Hispanic/Latino men, but not Black men, are significantly lower. Increased attention is needed to better understand the reasons behind these racial disparities and to develop effective interventions to promote access.